2006
DOI: 10.3136/fstr.12.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citrus Fruit (Sudachi) Juice on Absorption of Calcium from Whole Small Fish in Healthy Young Men

Abstract: Shirasuboshi (boiled and semi-dried whitebait) is a processed seafood that is abundant in calcium. It is eaten whole and commonly consumed in Japan. In this study, we examined the e#ect of Sudachi (Citrus sudachi Hort. ex. Shirai) juice on calcium, magnesium and phosphorus bioavailability in healthy young men. Dried shirasuboshi powder treated with distilled water (C) or sudachi juice (S,*) was prepared for use in two experimental diets, the control diet and the sudachi diet. Either S,* or C was added to a bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In addition, an investigation on the consumption of lemon juice, walking, and blood pressures in 33–77 year-old Japanese women showed that blood citric acid concentrations negatively correlated with the changes in blood pressure [ 66 ]. Citric acid may promote the absorption of calcium and magnesium that could affect blood pressure [ 67 , 68 , 69 ]. However, the relationship between citric acid intake and its effect on metabolic syndrome is still inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an investigation on the consumption of lemon juice, walking, and blood pressures in 33–77 year-old Japanese women showed that blood citric acid concentrations negatively correlated with the changes in blood pressure [ 66 ]. Citric acid may promote the absorption of calcium and magnesium that could affect blood pressure [ 67 , 68 , 69 ]. However, the relationship between citric acid intake and its effect on metabolic syndrome is still inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Nii et al [30] has previously demonstrated that, in rats, the consumption of shirasuboshi together with sudachi (Citrus sudachi) juice leads to significant decreases in the concentrations of urinary pyridinoline and deoxypyridinoline and inhibits bone resorption. They have also reported that, in healthy male students, a diet containing shirasuboshi and sudachi juice promotes the absorption of minerals such as Ca and magnesium [31].…”
Section: Changes In the Concentrations Of Bone Metabolism Markersmentioning
confidence: 95%
“…Citric acid was the most abundant phytochemical quantified in this study (with beef from GRASS containing 379.20 mg of citric acid per 100 g of beef). Citric acid is mostly found in fruits, especially citrus fruits, and has several health benefits, including increasing the bioavailability and absorption of minerals and reducing risks of kidney stone formation [85,86]. Supplee and Bellis [87] noted that pasture feeding may increase concentrations of citric acid in milk in some instances.…”
Section: Phytochemical Profile Of Beefmentioning
confidence: 99%